Association between extremely preterm caesarean delivery and maternal depressive and anxious symptoms: a national population‐based cohort study. (8th October 2020) - Blanc, J; Rességuier, N; Lorthe, E; Goffinet, F; Sentilhes, L; Auquier, P; Tosello, B; d'Ercole, C
Abstract : Objective: To evaluate whether caesarean delivery before 26 weeks of gestation was associated with symptoms of depression and anxiety in mothers in comparison with deliveries between 26 and 34 weeks. Design: Prospective national population‐based EPIPAGE‐2 cohort study. Setting: 268 neonatology departments in France, March to December 2011. Population: Mothers who delivered between 22 and 34 weeks and whose self‐reported symptoms of depression (Center for Epidemiologic Studies Depression Scale: CES‐D) and anxiety (State‐Trait Anxiety Inventory: STAI) were assessed at the moment of neonatal discharge. Methods: The association of caesarean delivery before 26 weeks with severe symptoms of depression (CES‐D ≥16) and anxiety (STAI ≥45) was assessed by weighted and design‐based log‐linear regression model. Main outcome measures: Severe symptoms of depression and anxiety in mothers of preterm infants. Results: Among the 2270 women completing CES‐D and STAI questionnaires at the time of neonatal discharge, severe symptoms of depression occurred in 25 (65.8%) women having a caesarean before 26 weeks versus in 748 (50.6%) women having a caesarean after 26 weeks. Caesarean delivery before 26 weeks was associated with severe symptoms of depression compared with caesarean delivery after 26 weeks (adjusted relative risk [aRR] 1.42, 95% CI 1.12–1.81) adjusted to neonatal birthweight and severe neonatal morbidity among other factors. There was no evidence of an association between mode of delivery and symptoms of anxiety. Conclusions: Mothers having a caesarean delivery before 26 weeks' gestation are at high risk of symptoms of depression and may benefit from specific preventive care. Tweetable abstract: Mothers having caesarean delivery before 26 weeks' gestation are at high risk of symptoms of depression. Tweetable abstract: Mothers having caesarean delivery before 26 weeks' gestation are at high risk of symptoms of depression.